Enhancing Students’ Logical-Thinking Ability in Natural Science Learning with Generative Learning Model - Henni Riyanti; Suciati Suciati; Puguh Karyanto (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
The logical-thinking ability is one of the important competencies of 21st century that should be empowered. It is one of the aspects in a cognitive science domain that has not been implemented effectively in teaching and learning in the class. Then, this study aimed to analyzed the influence of generative learning model to enhance students' logical-thinking ability. This study was also conducted by using a quasi-experimental study with pretest-posttest non-equivalent control group design. The sample was chosen by using simple random sampling technique. This study involved two classes which had 67 participants consisting of 34 students in Class VIII.9 as an experimental group and 33 students in Class VIII.7 as a control group. The researcher used the instrument of logical-thinking ability formulated in the form of multiple choice tests with five alternative answers that had been tested for its validity and reliability. The analysis of data employed t-test using SPSS 21. The result indicated that the t-count t-table (2.44 1.99) and p-value = 0.017 (p 0.05). It could be concluded that the application of generative learning model resulted in a significant influence on students' logical-thinking ability. The result of the analysis could be used by the schools for evaluating the quality of natural science learning in order to encourage students’ logical-thinking ability.